Unveiling the enigma of spontaneous cervical swelling syndrome: A case report - Yazan Dumaidi; Ahmad Rjoub; Ahmad Meri; Ahmed Helou; Mohammed Barakat; Lotof Hamdan; Mahmoud Alawneh; Motaz Daraghma (Radiology Case Reports)
Spontaneous cervical swelling syndrome is an uncommon clinical syndrome characterized by the sudden onset of swelling in the cervical region with no identifiable cause. A 47-year-old woman with a history of Iron Deficiency Anemia presented to the emergency department (ED) complaining of an acute left neck and upper chest swelling and pressure sensation in her neck. The swelling started suddenly and was growing rapidly over several hours. There was no associated fever, cough, or history of trauma. Patient examination was found to be normal. Further investigation included X-Ray which showed tracheal deviation to the right side, and the Computed tomography showed soft tissue and subcutaneous edematous changes involving the left neck region and extending down to the left infraclavicular and mediastinal regions. Laboratory tests revealed elevated lactate dehydrogenase (LDH), erythrocyte sedimentation rate (ESR), and fibrinogen levels. The patient was admitted to the surgical Intensive care unit (SICU) for further monitoring and observation, at which she received intravenous fluids, hydrocortisone, pantoprazol, and paracetamol, accompanied by serial monitoring and physical examinations. One day after, the swelling has subsided, and the patient was trasnfered to the surgical ward after 1 day. The patient was sent home with safety netting instruction in case of shortness of breath.